ECONOMIC VIABILITY OF ARABICA COFFEE IN THE STATE OF ESPÍRITO SANTO CONSIDERING MANUAL AND SEMI-MECHANIZED HARVEST - GALEANO, EDILEUZA VITAL; Krohling, Cesar Abel (Coffee Science - ISSN 1984-3909, 2019)
Recent studies have shown that coffee production costs have been rising above inflation and that the activity has become less attractive to producers. One of the ways to try reducing costs is through the mechanization of activities. The objective of this study was to evaluate the production cost and economic viability of arabica coffee in the state of Espírito Santo, comparing manual and semi-mechanized harvest to different yield levels. For the feasibility analysis, the techniques of Net Present Value and Internal Rate of Return were used and the sensitivity analysis was used for risk assessment. The results show advantages of semi-mechanized harvest. At the level of 50 bags per hectare, the activity was profitable considering the interest rate of 8%. In manual harvesting, the IRR is 8.3% and, in the semi-mechanized harvest, the IRR is 16%. Producers must invest in higher yield levels with new technologies and mechanization to have greater return in the activity.